Neolithic monuments: sensory technology. (2nd January 2017) - Was, John; Watson, Aaron
ABSTRACT: An examination of Neolithic monuments across the British Isles reveals how they may function as sensory technologies and how the auditory effects generated by these structures can profoundly impact upon our perceptions and responses. To consider the auditory properties of a site we must actively produce sound to energise its acoustic qualities. This 'active' interaction prompts a broader consideration of our past and present relationship with Neolithic monuments. We suggest that these sites be re-imagined as reactive spaces, fuelled by the actions and thoughts of people within. As such, monuments are potentially vibrant and still-active technologies that can transform perception and generate dynamic multisensory experiences.